Intravenous human immunoglobulin treatment of serum from HLA-sensitized patients in kidney transplantation. (May 2014) - Picascia, Antonietta; Grimaldi, Vincenzo; Paolillo, Rossella; Vasco, Maria; Casamassimi, Amelia; De Luca, Francesco Paolo; Cavalca, Francesco; Schiano, Concetta; Napoli, Claudio
Abstract Objective: Intravenous immunoglobulin (IVIG) products are known to have beneficial immunomodulatory effects on several inflammatory and autoimmune disorders. These effects could be attributed to a different inhibitory action on complement factors, but other mechanisms could be implicated, e.g., immunocomplexes development and/or anti-idiotypic antibodies. Positive results on the reduction of anti-Human Leukocyte Antigens (HLA) antibodies in highly sensitized patients have also been found. The present study focuses on the effect of IVIG on the reduction of Panel Reactive Antibody level and crossmatch positivity in sensitized patients awaiting kidney transplantation. Methods: The study was performed adapting an in vitro assay on sensitized patients' sera in waiting list for kidney transplantation. Sera of twelve highly sensitized patients were evaluated for the cytotoxicity inhibition after 10% IVIG treatment. Results: A reduction of anti- HLA antibody levels was observed in 75% (9/12) of treated patients in vitro, while 25% (3/12) resulted unresponsiveness. Particularly, our data showed a significantly higher Panel Reactive Antibody reduction for T lymphocytes (p < 0.010) than B lymphocytes (p < 0.032). Conclusions: In this study, we have used an in vitro assay to investigate susceptibility to desensitization with IVIG treatment of sensitized patient sera. These findings reveal that the variable effect of IVIG on reducing Panel Reactive Antibody in our immunized patients could be attributed to a different inhibitory action on complement, likely due to the type and the titre of anti-HLA antibodies.